2017
DOI: 10.22271/tpr.2017.v4.i3.054
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas putida and Bacillus amyloliquefaciens alleviates the adverse effect of pesticides and poise soil enzymes activities in chickpea (Cicer arietinum L.) rhizosphere

Abstract: Abstract:Pesticide application for disease management is a major action for crop protection from last seven decades. The repeated application of pesticide is the most important cause of the reduction in microbial population. Soil microorganisms play an important role in efficient acquisition and transportation of nutrients to plant. Pesticides leached in soil disturb the activities of soil enzymes, such as β-glucosidase, dehydrogenase, phosphatases, protease and urease secreted by these microorganisms. This dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Thus, PGPR are emerging as organic fertilizers suitable for many plant species, which could reduce chemical fertilizer application while enhancing soil quality and plant yield [49]. The PGPR species Pseudomonas putida and Bacillus amyloliquefaciens decreased the negative impact of three pesticides (carbendazim, imidacloprid, and glyphosate), maintained soil enzyme activities, and enhanced soil health and fertility [50].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PGPR are emerging as organic fertilizers suitable for many plant species, which could reduce chemical fertilizer application while enhancing soil quality and plant yield [49]. The PGPR species Pseudomonas putida and Bacillus amyloliquefaciens decreased the negative impact of three pesticides (carbendazim, imidacloprid, and glyphosate), maintained soil enzyme activities, and enhanced soil health and fertility [50].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, siderophore (an iron chelating compound) are synthesized under Fe starved condition by microbial communities. This is useful because strains that produce siderophore might be employed in phytopathogens bio management ( Kumar et al., 2017 ). Siderophore ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Kumar et al . 77 reported that pesticide-tolerant PGPR strains P. putida and B. amyloliquefaciens alleviated the adverse effect of pesticides and increased soil enzyme activities and seed germination efficiency, elongated plant organs and enhanced other parameters of C. arietinum . These findings corroborate our facts that inoculated PGPR degrade/detoxify pesticides and thus, improve various parameters of legumes grown in the affected soil.…”
Section: Resultsmentioning
confidence: 99%